Application of Bottlebrush Block Copolymers as Photonic Crystals. Issue 13 (22nd May 2017) - Liberman‐Martin, Allegra L.; Chu, Crystal K.; Grubbs, Robert H.
Abstract : Brush block copolymers have emerged as promising components in the bottom‐up synthesis of photonic crystals from common organic chemical feedstocks. This polymer architecture permits fabrication of photonic crystal films under ambient conditions driven by self‐assembly. Photonic properties can be controlled by the backbone length of the brush block copolymer or by utilizing blending techniques. Abstract : Brush block copolymers are a class of comb polymers that feature polymeric side chains densely grafted to a linear backbone. These polymers display interesting properties due to their dense functionality, low entanglement, and ability to rapidly self‐assemble to highly ordered nanostructures. The ability to prepare brush polymers with precise structures has been enabled by advancements in controlled polymerization techniques. This Feature Article highlights the development of brush block copolymers as photonic crystals that can reflect visible to near‐infrared wavelengths of light. Fabrication of these materials relies on polymer self‐assembly processes to achieve nanoscale ordering, which allows for the rapid preparation of photonic crystals from common organic chemical feedstocks. The characteristic physical properties of brush block copolymers are discussed, along with methods for their preparation. Strategies to induce self‐assembly at ambient temperatures and the use of blending techniques to tune photonic properties are emphasized.